A violação dos direitos indígenas durante a ditadura militar no Brasil - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This study analyzes the systematic violations of indigenous peoples' rights during Brazil’s Military Dictatorship (1964-1985), focusing on the social, cultural, and territorial impacts on these communities. Under the guise of progress and national security, the authoritarian regime implemented policies that led to forced displacement, loss of ancestral lands, and the destruction of indigenous cultures. The National Indian Foundation (FUNAI), created to protect indigenous rights, often collaborated with economic exploitation projects, such as the construction of highways, hydroelectric dams, and the expansion of mining, prioritizing private interests while neglecting the demands of affected communities.The analysis reviews contributions from authors such as Darcy Ribeiro, Manuela Carneiro da Cunha, and Shelton Davis, who reveal how the Brazilian state used frameworks to enforce forced integration and acculturation policies, disregarding territorial and cultural rights. It highlights the use of the 1973 Indigenous Statute, which institutionalized control and assimilation practices, framing indigenous peoples as obstacles to development.The study also explores the relationship between the regime’s economic policies, including the so-called “economic miracle,” and the massacres of indigenous communities, exemplified by tragic events such as the Waimiri-Atroari genocide during the construction of the BR-174 highway. Additionally, it addresses the contemporary consequences of this repression, including the ongoing struggle for reparations and the persistence of predatory practices in indigenous territories.Finally, the work emphasizes the need to preserve historical memory and strengthen policies to protect indigenous peoples, highlighting their resilience and resistance in the face of structural violations perpetrated by the state.
Keywords: Governo militar – Brasil; Indígenas da América do Sul - Posse da terra – Brasil; Perseguição política; Indígenas - Estatuto legal, leis, etc.; Indígenas da América do Sul – Brasil; Aculturação; Direitos humanos; Military government – Brazil; Indigenous people of South America - Land tenure – Brazil; CNPQ::CIENCIAS HUMANAS